Development and Evaluation of Biotin Functionalized Fullerenes for the Delivery of Irinotecan to Colon Tumors - Dhiman, Shikha; Kaur, Amardeep; Gupta, Girdhari L.; Sharma, Manu (Current Drug Delivery, 2023)
Background: Irinotecan is a promising antitumor agent approved by FDA for intravenous use in colon cancer treatment either alone or in combination. It is a topoisomerase inhibitor and by blocking the topoisomerase-I enzyme, it causes DNA damage and results in cell death. However, it lacks selectivity and specificity for tumor cells, resulting in systemic toxicity. Thus, it is essential to reduce its side effects and improve therapeutic efficacy. Objective: The study aimed to improve the therapeutic efficacy and minimize the toxic effects of irinotecan by developing a fullerene functionalized biotin drug delivery system and adsorbing irinotecan on the surface of the functionalized fullerene-biotin complex. Methods: Fullerene (C60) has been observed as a potential drug delivery agent and the aminefunctionalized C60-NH2 was synthesized by functionalizing ethylenediamine on the surface of C60. The PEI functionalized C60 was further synthesized by polymerization of aziridine on the surface of C60- NH2. Biotin was attached by an amide linkage to C60-PEI and the anti-colon cancer drug irinotecan (IRI) was encapsulated (C60-PEI-Biotin/IRI). The C60-PEI-Biotin/IRI was characterized and evaluated for in vivo anti-colon cancer activity in rats and the results were compared with the parent drug irinotecan. Results: The results showed that C60-PEI-Biotin/IRI conjugate had a controlled release profile according to in vitro HPLC studies. Moreover in vivo anti-tumor studies suggested that the conjugate proved to be less toxic to vital organs and had high efficacy towards tumor cells. Statistical studies confirmed less tumor index and tumor burden in the case of conjugate when compared to irinotecan. Conclusion: It is hypothesized that the conjugate (C60-PEI-Biotin/IRI) could cross the cell membrane easily through overexpressed biotin receptors on the cell surface of colon cancer cells and showed better efficacy and less toxicity in comparison to IRI in the colon cancer rat model.
Keywords: nanoparticles